Retrospective analysis of Syrian refugee patients admitted to a hospital adult emergency service - Ensar Durmuş; Fatih Güneysu (SERNEV, 2021)
Introduction: Due to wars and political changes, large-scale migration can occur from countries. Millions of people leave their places of residence and take refuge in other countries and affect the sociological, economic and health systems of the country they go to. Methods: Syrians under temporary protection, who applied to Sakarya University Training and Research Hospital adult emergency room between 01/03/2018-31/12/2019, were examined retrospectively. Thus, it was aimed to examine the effect of Syrian refugees on emergency services. Results: A total of 4310 Syrian patient applications are made, of which 2710 are male and 1600 are female. 3607 (83.7%) of the patients applied to the green outpatient clinic, 175 of the patients (4.1%) are forensic cases. 151 (86.3%) of forensic cases belong to male Syrian patients. Most of the patients are young adults, the average patient age is 30.8 ± 10.71 and the median age is 28. Conclusion: It was concluded that Syrians mostly apply to the green clinic in the adult emergency department, male and young patients apply more, forensic cases occupy a small proportion among these applications, and generally non-emergency cases use the emergency service. Refugees can be informed about applying to primary health care in non-emergency situations and organizing health infrastructure in this direction can reduce the emergency service workload.